o the description of the subbarier particles' moving - A. K. Zaichenko (Ядерна фізика та енергетика)
The approximate expressions for the nonstationary wave functions, describing the movement of the particles under the rectangular potential barrier, and their parameters are obtained. Simple method of more accurate determination of these values is proposed.